DIGITIZATION OF TEACHING QAWÂID ‘ARABIYYAH AT UIN FATMAWATI SUKARNO BENGKULU / DIGITALISASI PEMBELAJARAN QAWÂID ‘ARABIYYAH DI UIN FATMAWATI SUKARNO BENGKULU - Achmad Ja'far Sodik; Muhammad Kholilur Rosyid; Nurlaila Nurlaila; Wildana Wargadinata; Syukran Syukran (Lughawiyah: Journal of Arabic Education and Linguistics, 2023)
This study aims to determine the digitization model of teaching qawâid arabiyah at UIN FAS Bengkulu, the supporting factors for the process of digitization, and the implications in learning Arabic. The descriptive qualitative approach was used in this study. The information was collected through observations conducted when teaching qawâid arabiyah in Arabic learning, as well as interviews with lecturers and students at UIN FAS Bengkulu. Miles and Huberman's interactive analysis was used in this study, which begins with collecting data, presenting, reducing, and concluding it. The results of this study indicate that the digitization of teaching qawâid arabiyah at UIN FAS Bengkulu is in the form of digitizing learning materials, digitizing supporting media, and digitizing learning assessment. Factors supporting the process of digitizing qawâid arabiyah are the availability of adequate technological facilities, the existence of creative teaching staff, and the existence of learning innovation ideas. The implications of the digitization process of teaching qawâid arabiyah in learning Arabic include that learning becomes more interesting, students are excited about participating in learning and are actively involved in the learning process, and students’ achievement improves.